Dynamic Gains From Trade : Evidence From South Africa - Subramanian, Arvind (IMF Working Papers; Working Paper ;, 2000)
This paper examines the empirical relationship between trade and total factor productivity (TFP) in South Africa. It uses (i) a time series approach where trade is defined in terms of aggregate outcomes, id est, as the share of imports plus exports in GDP, and (ii) a cross sectional approach, where trade is defined in terms of trade policy, id est, as actual trade protection across different manufacturing sectors. The results indicate that there is a significant positive relationship between trade and TFP growth both over time and across sectors.